PSYCHOTHERAPEUTIC DIAGNOSTICS IN THE STRUCTURE OF EDUCATIONAL PROJECTS - Католик, Галина Вікторівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
An article examines the structure of initial psychotherapy interview, which in turn forms the basis for the diagnosis of personal and professional areas of self-concept of a practical psychologist who is trained in the educational project. As a part of the professional selection of candidates for the educational project of the integrative psychodynamic psychotherapy of children and youth is seen substantial part of the author’s psycho diagnostic system